Upaya Pencegahan dan Pemberdayaan Ekonomi Masyarakat Terdampak Covid-19 di Kecamatan Kademangan Kota Probolinggo - Husni Mubaroq; Nur Halima (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2021)
The covid-19 virus is a virus that spreads through droplets between humans and comes in direct contact with objects exposed to the virus. The increase in active cases of Covid-19 in Probolinggo City, especially Kademangan District, is because the community is still lacking information about the spread and prevention of Covid-19. As a result, many people have been affected economically due to the Covid-19 pandemic. The purpose of this community service is to prevent the spread of the Covid-19 virus, foster healthy living patterns, and empower the economy of people affected by Covid-19. Our service partners are the managers of the Bayuangga terminal and Bakpia Manalagi UMKM. Methods of community service in the form of education about 3M, and distribution of hand washing assistance at the Bayuangga Terminal, as well as empowering Bakpia Manalagi MSMEs by helping expand marketing with digital marketing methods. With community service that has been carried out, an understanding of the importance of doing 3M when activities outside the home and by expanding marketing using digital marketing is able to increase the demand for products which has an impact on the need for employees who can empower the surrounding community.Keywords : Covid-19, healthy lifestyles, digital marketing, Covid-19 prevention, Community empowerment